Pengaruh Penambahan Crude Extract Cengkih (Oleoresin) (Syzygium aromaticum) sebagai Antimikroba pada Fillet Ikan Nila (Oreochromis niloticus) - Lailqadrisha Sakina, Rahmadita
Production of fishery products always increases per year due to the needs of the world. As the second largest producer in the world aquaculture sector, Indonesia produces the second highest tilapia production in Indonesia. Tilapia fillets are the common form of market demand, but fillets are rapidly declining due to damage caused by microbes. Natural antimicrobials derived from clove oleoresin compounds were added to maintain its quality. The purpose of this study was to determine the effect of the combination treatment of adding crude extract of oleoresin cloves at concentrations of 1%, 2%, and 3% with variations in the storage time and storage temperature of tilapia fillets on microbial activity observed and tested based on total plate count (TPC), Vibrio sp., Escherichia coli, Salmonella sp., Aeromonas and Pseudomonas. Fillets of tilapia are stored for 15 and 30 days with variations in temperature of 28 ° C, 4 ° C and -4 ° C. The storage results of tilapia fillets work best at freezing temperatures (-4 ° C). The increase in the number of microbes increased and reached a high number at 30 days of storage. The antimicrobial activity of oleoresin had an effect on the results of the Total Plate Count and total Vibrio numbers which showed significant changes (P <0.05) in each variation, but no significant difference (P> 0.05) in the testing of E. coli, Salmonella sp., Aeromonas and Pseudomonas. The most optimum treatment given to tilapia fillets is by adding 3% clove oleoresin and stored at freezing temperature (-4 °C) because it has the best microbial analysis results.